Geranylgeranyltransferase I of Candida albicans: Null Mutants or Enzyme Inhibitors Produce Unexpected Phenotypes - Kelly, Rosemarie (American Society for Microbiology, 2000)
Geranylgeranyltransferase I (GGTase I) catalyzes the transfer of a prenyl group from geranylgeranyl diphosphate to the carboxy-terminal cysteine of proteins with a motif referred to as a CaaX box (C, cysteine; a, usually aliphatic amino acid; X, usually L). The α and β subunits of GGTase I from Saccharomyces cerevisiae are encoded by RAM2 and CDC43, respectively, and each is essential for viability. We are evaluating GGTase I as a potential target for antimycotic therapy of the related yeast, Candida albicans, which is the major human pathogen for disseminated fungal infections. Recently we cloned CaCDC43, the C. albicans homolog of S. cerevisiae CDC43. To study its role in C. albicans, both alleles were sequentially disrupted in strain CAI4. Null Cacdc43 mutants were viable despite the lack of detectable GGTase I activity but were morphologically abnormal. The subcellular distribution of two GGTase I substrates, Rho1p and Cdc42p, was shifted from the membranous fraction to the cytosolic fraction in the cdc43 mutants, and levels of these two proteins were elevated compared to those in the parent strain. Two compounds that are potent GGTase I inhibitors in vitro but that have poor antifungal activity, J-109,390 and L-269,289, caused similar changes in the distribution and quantity of the substrate. The lethality of an S. cerevisiae cdc43 mutant can be suppressed by simultaneous overexpression of RHO1 and CDC42 on high-copy-number plasmids (Y. Ohya et al., Mol. Biol. Cell 4:1017, 1991; C. A. Trueblood, Y. Ohya, and J. Rine, Mol. Cell. Biol. 13:4260, 1993). Prenylation presumably occurs by farnesyltransferase (FTase). We hypothesize that Cdc42p and Rho1p of C. albicans can be prenylated by FTase when GGTase I is absent or limiting and that elevation of these two substrates enables them to compete with FTase substrates for prenylation and thus allows sustained growth.